2020
DOI: 10.3390/su12083116
|View full text |Cite
|
Sign up to set email alerts
|

Quantities and Quantification Methodologies of Food Waste in Swedish Hospitals

Abstract: To move towards a sustainable food system, we cannot continue to waste substantial amounts of the food produced. This is especially true for later stages in the food supply chain, where most sub-processes consume resources in vain when food is wasted. Hospitals are located at the end of the food supply chain and the sector has high levels of food waste. This study investigated food waste quantification practices in Swedish hospitals, examined whether a questionnaire is an appropriate methodology for such mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Following implementation, re‐auditing waste using the same methods is required to demonstrate the outcomes of the intervention 11,42 . This may illustrate a decrease in waste as demonstrated by hospitals with a long history of quantifying food waste reporting a trend of decreasing waste over time 53 . Nutrition and dietetics professionals can lead in the implementation and interpretation of the data that arise from these hospital food waste audits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Following implementation, re‐auditing waste using the same methods is required to demonstrate the outcomes of the intervention 11,42 . This may illustrate a decrease in waste as demonstrated by hospitals with a long history of quantifying food waste reporting a trend of decreasing waste over time 53 . Nutrition and dietetics professionals can lead in the implementation and interpretation of the data that arise from these hospital food waste audits.…”
Section: Discussionmentioning
confidence: 95%
“…11,42 This may illustrate a decrease in waste as demonstrated by hospitals with a long history of quantifying food waste reporting a trend of decreasing waste over time. 53 Nutrition and dietetics professionals can lead in the implementation and interpretation of the data that from these hospital food waste audits. The use of best practice guidelines is not unfamiliar to hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Gustavson et al [4] estimated that one-third of the global food production is either lost or wasted; some studies, such as Neff et al [5] and Qi and Roe [6] indicated that consumers hesitate to consume food items that are past their prime state and prefer fresh food to reduce health risks; therefore, food losses and waste from private households account for a major share of total food loss and waste, especially in developed countries. Moreover, restaurants and food services account for a significant proportion of food wastage and have been identified as an important unsustainability hotspot [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the consumption link, scholars have focused on waste on the dining table, that is, food surplus on the plate [11,12]. In developed countries, researches mainly focus on restaurants [13], households [14], hospitals [15], and schools [16].…”
Section: Introductionmentioning
confidence: 99%